An Effectiveness of High Order Thinking Skills (HOTS) Self-Instructional Manual for Students’ Assignment Achievement - Hamdan, Nuraffefa; Tze Kiong, Tee; Mei Heong, Yee; Masran, Saiful Hadi; Md Yunos, Jailani; Mohamad, Mimi Mohaffyza; Hj Azid, Nurulwahida; Othman, Widad; Hanapi, Zaliza; Azman, Mohamed Nor Azhari; Haris, Mohd Hairol Mizzam; Shafei, Suzana (Journal of Technical Education and Training, 2019)
High Order Thinking Skills (HOTS) is an important aspect of teaching and learning. One’s thinking can affect learning ability, learning speed and effectiveness of learning. The weakness in implementing HOTS is the reason for a student not creative in solving all the problems that arise. The purpose of this study is to evaluate the effectiveness of HOTS’s Self-Instructional Manual (SIM) in teaching and learning for assignment achievement among polytechnic students. This study uses a quantitative approach and the Quasi Experimental design - “Pretest-Posttest Nonequivalent Comparison Group Design” consisting of one Treatment Group (TG) and one Control Group (CG) involving 78 students at Polytechnic of Sultan Abdul Halim Muad’zam Shah. The assignment evaluation rubric was modified to assess the level of student assignment achievement. The findings showed that most of the students for TG and CG achieved good result in the individual pre assignment. Additionally, there is a significant difference mean scores of individual post assignment between TG and CG. Students for TG achieved excellent result in the individual post assignments. However, students for CG only achieved good result in the individual post assignments. This means that HOTS Self-Instructional Manual has a significant impact on the student assignments achievement. Therefore, we encourage all students of higher education institutions to use Self-Instructional Manual in teaching and learning in order to score better achievement especially in the course work